Izobraževanje odraslih za trajnostni razvoj v luči teorij transformativnega učenja - Košmerl, Tadej (Sodobna pedagogika, 2022)
This article discusses the importance of adult education for sustainable development in light of the 2030 Agenda for Sustainable Development adopted by the United Nations in 2015. It exhibits that the agenda’s Sustainable Development Goals are based on two fundamentally incompatible philosophies and that the central question of (adult) education for sustainable development is who and what should transform—and to what extent. For this reason, the theory of transformative learning and its different approaches to adult education are discussed. Based on a literature review, we argue that adult education for sustainable development meets its desired outcomes when changes in thinking, emotions and actions are reflected in individuals’ worldviews, epistemology, ontology and behaviours in such a way that irreversibly changes their way of living in the world, as well as when such education is based on ontologies of relationality that assume the interrelations of all forms of life.
Keywords: adult education; andragogika; education; izobraževanje odraslih; Jack Mezirow; pedagogika; pedagogy; sustainable development; trajnostni razvoj; transformative learning; transformativno učenje; vzgoja in izobraževanje